The race set before us a biblical theology of perseverance and assurance - Schreiner, Thomas R.; Caneday, Ardel B. (Downers Grove, IL IVP, 2001)
Includes bibliographical references and index.
Keywords: Perseverance (theology) -- biblical teaching; Assurance (theology) -- biblical teaching; Christine life -- biblical teaching; Bible. N.T. -- criticism, interpretation, etc